The genome sequence of the Slender-footed Robberfly, Leptarthrus brevirostris (Meigen, 1804) [version 1; peer review: 2 approved] - Robert Wolton (Wellcome Open Research, 2025)
We present a genome assembly from a female specimen of Leptarthrus brevirostris (Slender-footed Robberfly; Arthropoda; Insecta; Diptera; Asilidae). The assembly contains two haplotypes with total lengths of 850.81 megabases and 851.46 megabases. Most of haplotype 1 (99.05%) is scaffolded into 6 chromosomal pseudomolecules. Haplotype 2 was assembled to scaffold level. The mitochondrial genome has also been assembled, with a length of 18.16 kilobases.